Longitudinal trends in utilization of endocrine therapies for breast cancer: an international comparison. (4th November 2014) - Kelly, E.; Lu, C. Y.; Albertini, S.; Vitry, A.
Summary What is known and objective Endocrine therapy is an effective treatment for post‐menopausal women with 'oestrogen receptor‐positive' invasive breast cancers. There are two main types of endocrine therapies: selective oestrogen receptor modulators (tamoxifen) and aromatase inhibitors (anastrozole, letrozole and exemestane). The aim of this study was to compare the patterns of use of endocrine therapies for breast cancer in women between nine developed countries. Methods A longitudinal, cross‐national drug utilization study was conducted. The endocrine therapies included were tamoxifen and the aromatase inhibitors: anastrozole, letrozole and exemestane. Annual drug utilization data were collected from Australia, Denmark, England, Finland, France, Iceland, the Netherlands, Norway and Sweden over the period 2001–2012. Utilization was measured in DDD/1000 inhabitants/day and was also adjusted for breast cancer incidence and female population statistics. Results and discussion Total use of endocrine therapies either increased or remained steady in all countries. Total endocrine therapy usage was consistently highest in England and France. Norway showed the lowest usage of endocrine therapies overall, using only 1·80 DDD/1000 inhabitants/day in 2012. Downward trends in tamoxifen use and upward trends in aromatase inhibitors were seen across all countries over the study period. By 2012, aromatase inhibitors represented over half of total endocrine therapy use in all countries, and as high as 74% and 80% in France and Denmark, respectively. What is new and conclusion Our analysis found a shift in use of endocrine therapy from tamoxifen to aromatase inhibitors. This trend is consistent with major clinical guidelines endorsing preferential use of aromatase inhibitors in post‐menopausal women. Stabilization or small increase in tamoxifen use in the recent years may reflect the recognition of tamoxifen as still an appropriate first‐line treatment. The similarity in utilization patterns may be due to the relatively comparable healthcare systems in the countries, namely universal health insurance and pharmaceutical coverage. Differences in utilization observed could be due to differences in breast cancer incidence, prescribing behaviours, interpretation of new trial evidence, and timing of drug marketing approval and reimbursement between countries.